Hydrogen Reactivity of Palladium Nanoparticles Coated with Mixed Monolayers of Alkyl Thiols and Alkyl Amines for Sensing and Catalysis Applications - Moreno, Monica (2011)
Pd monolayer-protected clusters (MPCs) coated with octylamines (C8NH2), hexanethiolates (C6S), and mixed monolayers of C8NH2 and C6S exhibit significantly different reactivities with hydrogen gas, depending on the relative amounts of the two ligands coating the Pd nanoparticle surface, as determined by UV-vis spectroscopy of Pd MPCs in solution and electronic measurements of films of Pd MPCs as a function of exposure time to hydrogen.  The average estimated composition of the ~ 3.0 nm diameter Pd MPCs was Pd919(C8NH2)177-x(C6S)x, where x was varied to be 0, 3, 10, 16, 32, 81, or 192 by the synthesis of pure C8NH2 Pd MPCs and subsequent liquid-phase place-exchange with a varied amount of C6SH.  When x = 0-10, the Pd MPCs react strongly with H2, leading to aggregated particles in solution and large irreversible changes in the morphology of films accompanied by an increase in film conductivity by 2-5 orders of magnitude.  When x = 192, the Pd MPCs are stable against aggregation in solution and do not exhibit large film morphology changes, but they are also not highly reactive to H2 as determined by minimal changes in the optical properties of solutions and the small, irreversible changes in the conductivity of films in the presence of H2.  Finally, when x = 16, 32, and 81, the Pd MPCs are fairly stable, exhibit minimal aggregation or morphology changes, and readily react with H2 based on the significant, reversible changes in film conductivity in the presence of H2.  Pd MPCs with mixed monolayers have the benefit of high H2 reactivity while maintaining the structural stability necessary for sensing and catalysis applications.